Heatwave-amplified atmospheric oxidation in a multi-province border area in Xuzhou, China - Zhang, Guoxian; Yu, Xingyu; Yin, Hao; Feng, Chunli; Ma, Chao; Sun, Shiqiang; Cheng, Haoqiang; Wang, Shiyu; Shang, Kunqi; Liu, Xiaoyan (Frontiers in Environmental Science, 2024)
Ozone formation is closely tied to emissions of precursors, meteorological conditions, and atmospheric chemistry. In June 2024, Xuzhou City, located at the intersection of Jiangsu, Shandong, Henan, and Anhui provinces in East China, experienced a series of ozone pollution events. The continuous pollution episodes were characterized by consistently high levels of ozone, with daytime peaks reaching 130 ppb. By combining observations of atmospheric oxidation and the use of the Observation-Based Model model, it was determined that the pollution was the result of a “heatwave-ozone” co-occurring extreme event triggered by elevated temperatures, low humidity, and intense radiation. The heatwave led to increased emissions of VOCs from both natural and human-related sources, with more pronounced contribution from Bio-alkenes and OVOCs. This, in turn, resulted in higher levels of oxidizing agents and ozone formation potential, exacerbating the co-occurrence of heatwaves and ozone extremes. Sensitivity tests on enhanced controls showed that reducing NOx had a significant adverse effect on ozone levels, whereas reducing VOCs had positive benefits, particularly for controlling alkenes. Despite ongoing reductions in anthropogenic VOCs, the elevated temperatures led to an increase in natural VOCs emissions. On average, a 1°C temperature decrease could reduce the reactivity ratio of VOCs to NOx (VOCR/NOxR) by 0.12, thereby enhancing the advantages of emission reductions. Therefore, implementing measures to alleviate extreme heatwaves, such as limiting high-energy consumption and inducing artificial rainfall, can simultaneously reduce the intensity and reactivity of VOC emissions, aiding in the effective implementation of ozone pollution control policies.